Effects of allelochemicals from tobacco root exudates on seed germination and seedling growth of tobacco - Huiyong, Yu (2014)
The composition of root exudates from two varieties (K 326 and NC 89) of tobacco were identified by GC-MS. Organic acids,amides and esters were the main constituents of the root exudates which differed in their qualitative and quantitative composition.Contents of cinnamic acid and nine other organic compounds was reduced in about 29% after 15 days of exposition to soil microflora.The effects of 6 organic acids (benzoic, cinnamic, lauric, myristic, palmitic and phthalic acids) identified intothe root exudates of tobacco varieties were evaluated on seed germination of tobacco.The cinnamic and benzoic acids were the most inhibitory on seed germination.